Penyuluhan tentang Pemberian Vitamin C terhadap Peningkatan Kadar Hemoglobine pada Ibu Hamil - Choralina Eliagita; Nuril Absari; Mika Oktarina (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Anemia can occur in women, especially pregnant women and breastfeeding mothers. This can happen because many pregnant and breastfeeding women suffer from iron deficiency. Providing additional iron is one of the government's efforts to overcome the incidence of anemia during pregnancy, childbirth, postpartum and breastfeeding. During the pregnancy process, each pregnant woman is given 90 Fe tablets for 90 consecutive days. Consuming fruits containing vitamin C can increase non-heme absorption by four times and plays an important role in iron absorption. The aim of this service is to educate pregnant women about how to increase hemoglobin levels by consuming FE tablets containing vitamin C. One way to provide this education is through pamphlets explaining the benefits of vitamin C in increasing hemoglobin levels in pregnant women. The purpose of the evaluation in this service is to carry out pre and post tests on pregnant women. The statistical test used is the paried sample t-test. As a result, the mother's level of knowledge before and after counseling using the booklet increased. In conclusion, the presence of counseling tools in the form of pamphlets makes it easier for pregnant women to understand the existing information.